(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2015)
يتناولُ هذا البحثُ إسنادَ الفعلِ الثلاثي المجرَّد إلى الضمائر في أزمنته الثلاثة: الماضي والمستقبل والأمر، وقد عرضنا فيه الأحوالَ المختلفةَ لتصريف الفعلِ مُسْنَدَاً إلى ضمائر الرفعِ المتصلةِ والمستترةِ ـ في كلٍّ من العبرية والعربية ـ وحاولنا تبيانَ ما يصيبُ الفعلَ من تغيُّرٍ لفظي يتعلَّقُ بالحركات والأحرف، كالبناء على ما يناسبُ الضميرَ المتصلَ، وكذلك الحذف، والزيادة، والإظهار، والإدغام، والإعلال، والإبدال. ولا شكَّ أنَّ معرفةَ هذه التغيُّرات الصوتية تساهمُ، بشكلٍ كبيرٍ، في تعلُّمِ اللغةِ العبريةِ لمن يريدُ تعلُّمها، كما تساعدُ دارسَ اللغةِ العربيةِ على فهمِ لغتهِ بصورةٍ أعمقَ، وأكثرَ دقَّةً واتِّساعاً، وذلك من خلال معرفةِ هذه التغيُّرات والتقعيدِ لها. This paper examines the attribution of abstract tripartite verb to the pronouns in its three tenses: past and future and imperative. We presented the various forms of verb conjugation attribute to attached and hidden subject pronouns – both in Arabic and Hebrew – and we tried to reflect what actually changed the movements and verbal characters, as based on what is appropriate to the attached pronoun, as well as deletion, and the increase, and the diphthong, conjugation, and substitution. There is no doubt that these phonetic changes knowledge contributes significantly to learning Hebrew for who wants to learn it, and helps Arabic language learners also helps to understand his language deeply, in a more refined and broadened way, by knowledge of the changes and standardization them